Suspension System Control Based on Type-2 Fuzzy Sliding Mode Technique. (24th May 2022) - Wang, Zheng; Ran, Longyi; Kong, Bing; Jia, Xuezeng; Liu, Liya; Tavoosi, Jafar
Abstract : This paper presents a new method of intelligent control for vehicle suspension. First, the suspension system is modeled with all the details, and then based on the obtained model, the sliding mode control is designed for it. The controller parameters and coefficients are calculated and updated by a type-2 fuzzy system. The chattering phenomenon is eliminated with a unique technique. In order to evaluate the performance of the proposed control system, two-model uncertainty of the road is applied. Simulations have been performed for both active and passive modes. The simulation results show the high efficiency of the proposed control system.